Private Activity in Water Shows Mixed Results in 2006 - World Bank (World Bank, Washington, DC, 2012)
In 2006, 12 low- and middle- income countries implemented at least 47 projects that involved investment commitments totaling US$2 billion according to just-released data from the Private Participation in Infrastructure Database. The annual number of water projects involving the private sector declined by 20 percent from the peak level of activity in 2005 and by 10 percent from activity in 2004, but still remained at one of the highest levels since 1995. Annual investment commitments stayed within the US$1-2 billion range of the past five years.